Feasibility of using Choosing by Advantages to improve multicriteria decision making in the subcontracting of precast concrete slabs in multifamily housing - Lopez De La Cruz, Bach Ing Oscar (2023)
Over the past few years, multi-family housing has been subject to increased complexity due to the demand in the housing market. Because of this, the subcontracting of precast concrete slabs is considered a good solution option due to its ample benefits such as time and labor savings. In addition, it is the most widely used structural element for this type of building. However, to obtain these benefits, a proper selection of precast concrete slab subcontractors is necessary. Therefore, it is necessary to have a selection method for the proper development of this process since a wrong decision will generate cost overruns and delays on site. Therefore, this research presents Choosing by Advantages (CBA) as a viable solution. The validation that is given through an expert judgment determines that the factors quality, delivery time and production capacity are the most important in the decision-making process. Finally, a multicriteria decision-making case was made for the subcontracting of precast concrete slabs highlighting the importance of the application of CBA in multi-family housing.